Performance of Iranian Naturally Fractured Cores under Miscible Displacement Experiments - Jamshidnezhad, M.; Sajjadian, V. A.; Montazer-Rahmati, M. M. (Journal of the Japan Petroleum Institute, 2004)
Determining the feasibility of miscible displacement process to increase oil recovery from Iranian naturally fractured reservoirs is the subject of this study. For that purpose, miscible displacement experiments including liquefied petroleum gas (LPG) injection were carried out under reservoir conditions on composite cores, consisting of reservoir fractured core plugs of the chosen rock type. Results of experimental studies indicated that LPG miscible flooding could maximize oil recovery. In this paper, results of the Iranian fractured core flooding experiments are presented.